Confessions of an ambivalent country expert: Queer refugeeism in the UK and the political economy of (im)mobility in and out of Trinidad and Tobago. (March 2019) - McNeal, Keith E.
This paper considers queer refugeeism from Trinidad and Tobago to the UK in relation to the political economy of (im)mobility in and out of the Caribbean. Gay rights have been embraced by liberal democracies as the newest form of human rights, what has been called "homonationalism." Mirroring other double-binds of liberal inclusion, I show how queer asylum-seekers get caught betwixt and between two globally-stratified homonationalisms while confronting the realpolitik of European asylum law not only as queer refugees but also in terms of transnational social mobility otherwise unavailable to them. The British asylum system therefore materializes as a bordering operation that more often than not denies lesbian, gay, bisexual and transgender (LGBT) asylum-seekers their rights under the sign of their humanitarian protection. I consider whether homonationalisms everywhere—as assemblages of human rights discourse—should be thought of as "post-political" projects, a concept critical to growing bodies of political theory and cultural critique. This is because humanitarianism touts "rights" as universal and moral, therefore transcending the political. However, as a result of their practical effects, I show how the institutional practices deemed post-political in the case at hand should be understood as attempts to deflect and defuse the underlying politics of socioeconomic status and mobility at stake, and that the conflicts and contradictions at the heart of queer asylum-seeking represent the return of the repressed political within legal-technical spaces of disagreement. I also scrutinize the ambivalent entanglements of "expertise" when anthropologists are solicited as country experts in legal asylum cases.